Fourier transforms of Lipschitz functions on the hyperbolic plane H2 - M. S. Younis (International Journal of Mathematics and Mathematical Sciences)
The purpose of the present work is to study the order of magnitude of the Fourier transforms fˆ(λ) for large λ of complex-valued functions f(z) sating certain Lipschitz conditions in the non-Euclidean hyperbolic plane H2.